A blended learning approach to teach fluid mechanics in engineering. (4th May 2017) - Rahman, Ataur
ABSTRACT: This paper presents a case study on the teaching and learning of fluid mechanics at the University of Western Sydney (UWS), Australia, by applying a blended learning approach (BLA). In the adopted BLA, various flexible learning materials have been made available to the students such as online recorded lectures, online recorded tutorials, hand written tutorial solutions, discussion board and online practice quizzes. The lecture and tutorial class times have been primarily utilised to discuss confusing topics and engage students with practical issues in applying the theories learnt in fluid mechanics. Based on the data of over 734 students over a 4-year period, it has been shown that a BLA has improved the learning experience of the fluid mechanics students in UWS. The overall percentage of student satisfaction in this subject has increased by 18% in the BLA case compared with the traditional one.